Apparatus for manufacturing negative electrode for secondary battery
By using a combination of a groove mold and coating roller in the negative electrode manufacturing apparatus, along with the application of a magnetic field and a drying section, the problem of low graphite orientation is solved, achieving efficient negative electrode manufacturing suitable for large-scale production and improved battery performance.
Patent Information
- Application Number
- CN202380038860.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-13
- Filing Date
- 2023-12-08
- Publication Date
- 2024-12-17
AI Technical Summary
Existing technologies make it difficult to achieve a high degree of crystal orientation of graphite in the manufacture of negative electrodes for secondary batteries, and are also difficult to apply to large-scale production.
An anode manufacturing apparatus is employed, comprising a trough mold and a coating roller. The upper and lower lips of the trough mold have magnetic properties of the same polarity. A magnetic field of 500G to 3,000G is applied, and coating is completed within 20 seconds in conjunction with a drying section, ensuring that the carbon-based anode active material is oriented and fixed before coating.
This technology enables efficient orientation of carbon-based anode active materials before coating, resulting in anodes with excellent orientation, suitable for mass production, and improved battery charging performance.
Smart Images

Figure CN119156715A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode manufacturing apparatus for a secondary battery and a method for manufacturing a negative electrode for a secondary battery using the negative electrode manufacturing apparatus for a secondary battery.
[0002] This application claims priority based on Korean Patent Application No. 10-2022-0173302 filed on December 13, 2022, the entire contents of which are incorporated herein by reference. Background Art
[0003] Recently, secondary batteries have been widely used not only in small devices such as portable electronic products but also in large and medium-sized devices such as battery packs or power storage devices in hybrid or electric vehicles.
[0004] This secondary battery refers to a rechargeable and dischargeable power generation device including a stacked structure of a positive electrode / separator / negative electrode. Generally, the positive electrode includes lithium metal oxide as a positive electrode active material, and the negative electrode includes a carbon-based negative electrode active material such as graphite, so that when the secondary battery is charged, lithium ions emitted from the positive electrode are adsorbed into the carbon-based negative electrode active material of the negative electrode, and when the secondary battery is discharged, the lithium ions contained in the carbon-based negative electrode active material are adsorbed into the lithium metal oxide of the positive electrode, and charging and discharging are repeated.
[0005] The negative electrode active material used in the negative electrode includes graphite materials such as natural graphite and artificial graphite. This graphite has a layered structure and is formed by stacking a plurality of layers in which carbon atoms form a network structure that unfolds in a planar shape. During charging, lithium ions can invade from the edges (layer overlap sides) of these graphite layers and diffuse between the layers, while during discharge, lithium ions can dissociate and release from the edges of the layers. In addition, since graphite has a lower resistance in the lateral direction of the layer than in the stacking direction of the layer, a conduction path for transferring electrons is formed along the lateral direction of the layer.
[0006] In this regard, in lithium secondary batteries using graphite, a technique for magnetically orienting the graphite contained in the negative electrode to improve the charging performance of the negative electrode has been traditionally proposed. Specifically, it has the following structure: wherein the [0,0,2] crystal plane of the graphite is oriented in a magnetic field when the negative electrode is formed so that it is approximately horizontal relative to the current collector and fixed therein. In this case, since the edge of the graphite layer faces the positive electrode active layer, the insertion and dissociation of lithium ions can be smoothly implemented, and the conduction path of the electrons is shortened, which can improve the electronic conductivity of the negative electrode, thereby improving the charging performance of the battery.
[0007] This orientation of graphite can be induced by coating a negative electrode slurry containing graphite on a current collector and applying a magnetic field to the undried negative electrode slurry. However, in the large-scale production of actual negative electrodes, it is difficult to ensure sufficient time to apply a magnetic field to induce graphite alignment of the negative electrode slurry, considering the production speed. In addition, if the intensity of the magnetic field applied to the negative electrode slurry applied to the electrode sheet is increased to solve this problem, the phenomenon of graphite being attracted by the magnetic field will occur at the end of the magnetic field, and the orientation of the graphite aligned perpendicular to the metal sheet will collapse, resulting in low orientation of graphite in the final manufactured negative electrode active layer.
[0008] Therefore, there is a need for a negative electrode manufacturing technology that can achieve a high degree of graphite orientation and is suitable for large-scale production of negative electrodes for secondary batteries.
[0009] [Related technical literature]
[0010] [Patent Document]
[0011] Korean Patent Publication No.10-2018-0048131 Summary of the invention
[0012] Technical issues
[0013] The present invention aims to provide a negative electrode manufacturing technology that can achieve a high degree of crystal orientation of a carbon-based negative electrode active material (such as graphite) contained in a negative electrode active layer while being suitable for large-scale production of negative electrodes for secondary batteries.
[0014] Technical Solution
[0015] In order to solve the above problems,
[0016] In one embodiment, the present invention provides,
[0017] A device for manufacturing an electrode sheet, on which a negative electrode slurry containing a carbon-based negative electrode active material is coated, the negative electrode manufacturing device for a secondary battery comprising:
[0018] a slot mold including an upper block, a lower block, and a slot for discharging negative electrode slurry through a gap between the upper block and the lower block; and
[0019] A coating roller, which is used to convey the electrode sheet coated with the negative electrode slurry discharged from the tank mold;
[0020] The upper block and the lower block include upper and lower lips forming outlets at their respective front ends, and the upper and lower lips exhibit magnetism of the same polarity to provide a negative electrode manufacturing device for a secondary battery.
[0021] In this case, the upper lip and the lower lip may have a structure including at least one of a permanent magnet and an electromagnet.
[0022] In addition, when the negative electrode slurry is discharged, a magnetic field having a strength of 500 G to 3,000 G can be applied.
[0023] In addition, the slot die can satisfy the following formula 1:
[0024] [Formula 1]
[0025] 0.3≤G / D≤5
[0026] (In Formula 1,
[0027] G represents the strength of the magnetic field applied at the upper lip and the lower lip (in G),
[0028] D represents the separation distance between the upper block and the lower block (unit: μm).
[0029] In addition, the negative electrode manufacturing apparatus may further include a drying section for drying the negative electrode slurry applied to the electrode sheet, wherein the drying section may be provided at a position where the negative electrode slurry discharged from the groove mold can reach within 20 seconds from the time when it is applied to the electrode sheet.
[0030] Furthermore, in one embodiment of the present invention,
[0031] Provided is a method for manufacturing a negative electrode for a secondary battery, comprising applying a negative electrode slurry to which a magnetic field is applied to an electrode sheet using a negative electrode manufacturing apparatus according to the present invention,
[0032] The negative electrode slurry contains carbon-based negative electrode active materials.
[0033] In this case, the average thickness of the negative electrode slurry applied to the electrode sheet may be greater than the separation distance between the groove of the groove mold provided in the negative electrode manufacturing apparatus and the coating roller, and the average thickness of the negative electrode slurry applied to the electrode sheet may be 100 μm or more.
[0034] In addition, applying the negative electrode slurry to the electrode sheet may be performed at a speed of 5 m / min to 100 m / min.
[0035] In addition, applying the negative electrode slurry to the electrode sheet may further include drying the applied negative electrode slurry to form a negative electrode active layer after applying the negative electrode slurry to the electrode sheet.
[0036] Here, the negative electrode active layer may have an alignment degree of the carbon-based negative electrode active material with respect to the surface of the electrode sheet of 0.9 or less, represented by the following Formula 2:
[0037] [Formula 2]
[0038] OI=I 004 / I 110
[0039] In formula 2,
[0040] I 004 It represents the area of the peak representing the [0,0,4] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer,
[0041] I 110 It represents the area of the peak representing the [1,1,0] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer.
[0042] Beneficial Effects
[0043] The negative electrode manufacturing device for a secondary battery according to the present invention can be applied in a state where the carbon-based negative electrode active material in the discharged negative electrode slurry is oriented nearly perpendicular to the surface of the current collector. Therefore, the manufactured negative electrode has the following advantages: not only has an excellent degree of orientation of the carbon-based negative electrode active material, but is also easy to apply to a large-scale production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a schematic cross-sectional view illustrating a negative electrode manufacturing apparatus for a secondary battery according to the present invention.
[0045] Figure 2 : is a perspective view illustrating the structure of a single die coater provided in the negative electrode manufacturing apparatus for a secondary battery according to the present invention.
[0046] Figure 3 is a conceptual diagram illustrating a principle of coating a carbon-based negative electrode active material in a negative electrode slurry to an electrode sheet in a self-aligned state by a single die coater according to the present invention. DETAILED DESCRIPTION
[0047] The present invention can have various modifications and various embodiments, and therefore, specific embodiments thereof will be described in detail below.
[0048] However, it should be understood that the present invention is not limited to the specific embodiments, and includes all modifications, equivalents, or substitutes within the spirit and technical scope of the present invention.
[0049] The terms "include", "comprising" and "having" used herein indicate the presence of the features, quantities, steps, actions, parts or components described in the specification, or a combination thereof, and it should be understood that the possibility of the presence or addition of one or more other features, quantities, steps, actions, parts, components, or a combination thereof is not excluded in advance.
[0050] In addition, in the present invention, when a part of a layer, film, region, plate, etc. is disposed "on" another part, this includes not only a case where a part is "directly" disposed "on" another part, but also a case where another part is interposed between them. Conversely, when a part of a layer, film, region, plate, etc. is disposed "under" another part, this includes not only a case where a part is "directly" disposed "under" another part, but also a case where another part is interposed between them. Furthermore, in the present application, "on" may include not only a case where it is disposed on an upper part, but also a case where it is disposed on a lower part.
[0051] In addition, in the present invention, "including as a main component" may mean including at least 50 wt.% (or at least 50 vol.%), at least 60 wt.% (or at least 60 vol.%), at least 70 wt.% (or at least 70 vol.%), at least 80 wt.% (or at least 80 vol.%), at least 90 wt.% (or at least 90 vol.%) or at least 95 wt.% (or at least 95 vol.%) of a defined component relative to the total weight (or total volume) of the negative electrode active material. For example, "including graphite as a main component of the negative electrode active material" may mean including at least 50 wt.%, at least 60 wt.%, at least 70 wt.%, at least 80 wt.%, at least 90 wt.% or at least 95 wt.% of graphite based on the total weight of the negative electrode active material, and in some cases may mean that the entire negative electrode active material is graphite (including at least 100 wt.% of graphite).
[0052] Furthermore, in the present invention, the "lip portion" refers to a region including an upper lip of an upper block and a lower lip of a lower block. The lip portion may include a spacing space formed between a plurality of lips (ie, a region where each lip is disposed in a groove).
[0053] Similarly, in the present invention, the "body part" refers to a region including an upper body of an upper block and a lower body of a lower block. The body part may include a spacing space formed between a plurality of bodies (ie, a region in which each body is disposed in a groove).
[0054] Hereinafter, the present invention will be described in more detail.
[0055] Negative electrode manufacturing device for secondary battery
[0056] In one embodiment, the present invention provides,
[0057] A device for manufacturing an electrode sheet, on which a negative electrode slurry containing a carbon-based negative electrode active material is coated, the negative electrode manufacturing device for a secondary battery comprising:
[0058] a slot mold including an upper block, a lower block, and a slot for discharging negative electrode slurry through a gap between the upper block and the lower block; and
[0059] A coating roller, which is used to convey the electrode sheet coated with the negative electrode slurry discharged from the tank mold;
[0060] The upper block and the lower block include an upper lip and a lower lip forming an outlet at each front end, and the upper lip and the lower lip exhibit magnetism of the same polarity.
[0061] The negative electrode manufacturing apparatus for a secondary battery according to the present invention is an apparatus for manufacturing a negative electrode used in a secondary battery, and has a configuration of manufacturing an electrode sheet by applying a negative electrode slurry including a carbon-based negative electrode active material to a current collector.
[0062] Specifically, Figure 1 2 is a cross-sectional view schematically illustrating the structure of a negative electrode manufacturing apparatus for a secondary battery according to the present invention. Figure 1 The negative electrode manufacturing device 10 includes a groove mold 100 and a coating roller 200 , and has a function of coating a negative electrode slurry onto a surface of an electrode sheet 300 while the electrode sheet 300 is moved by the rotation of the coating roller 200 .
[0063] In this case, if Figure 2 As shown, the slot mold 100 may have a discharge slot 140 formed between the upper mold 110 and the lower mold 120 at a position where the upper mold 110 and the lower mold 120 are opposite to each other, and the negative electrode slurry is discharged through the discharge slot 140. For example, the slot mold 100 may have a spacer 130 placed between the upper mold 110 and the lower mold 120 so that a gap is provided therebetween, thereby forming a channel through which the negative electrode slurry can move fluidly. In this case, the upper height and lower height of the slot may be determined by the thickness (in the Y-axis direction) of the first spacer 141 and / or the second spacer 142 that reflects the gap between the respective molds, and the thickness of the first spacer 141 and / or the second spacer 142 may be controlled according to the purpose or capacity of the secondary battery. Specifically, the thickness of each of the first spacer 141 and the second spacer 142 may independently be from 50 μm to 2,000 μm, more specifically, from 50 μm to 1,500 μm; from 500 μm to 1,200 μm; from 800 μm to 1,200 μm; from 80 μm to 200 μm; from 200 μm to 500 μm; or from 400 μm to 700 μm.
[0064] In addition, the spacer 130 has an opening 130a in which the first area is cut, and can be placed in all boundary areas except one of the respective opposite sides of the upper mold 110 and the lower mold 120. Therefore, a discharge outlet (in other words, a groove 140) for discharging the negative electrode slurry to the outside can be formed only between the front ends of the upper mold 110 and the lower mold 120. Here, the front end of the upper mold 110 and the front end of the lower mold 120 refer to the upper lip 111 and the lower lip 121, respectively, and the groove 140 for discharging the negative electrode slurry can be regarded as a place formed by the interval between the upper lip 111 and the lower lip 121.
[0065] In addition, the separator 130 is preferably made of a material having a sealing property, and prevents the negative electrode slurry from leaking into the gap between the upper mold 110 and the lower mold 120 except for the region where the groove 140 is formed, by functioning as a gasket.
[0066] In addition, the groove mold 100 is a single mold including an upper mold 110 and a lower mold 120, and one type of negative electrode slurry can be coated in a single layer on the negative electrode current collector. In this case, the upper mold 110 and the lower mold 120 may include an upper lip 111 and a lower lip 121 located at their respective front ends, and an upper body 112 and a lower body 122 extending from each lip and in close contact with the separator 130 to form a channel through which the negative electrode slurry can flow.
[0067] In addition, the upper lip 111 and the lower lip 121 may exhibit magnetism having the same polarity. Therefore, a magnetic field may be formed in the groove 140 formed by the upper lip 111 and the lower lip 121 in the same direction as the discharge direction of the negative electrode slurry.
[0068] like Figure 3As shown, if the path of negative electrode slurry discharge and coating is divided into an unoriented section A and an oriented section B, the carbon-based negative electrode active material (CM, such as graphite) of the negative electrode slurry is not affected by the magnetic field in the unoriented section A including the spaced-apart space between the upper body 112 and the lower body 122 (in other words, I: the main body) and thus moves in a state with a high degree of freedom. However, the oriented section B includes a separation space of the upper lip 111 and the lower lip 121 that exhibit the same polarity of magnetism (in other words, II: the lip portion). In the lip portion, due to the application of a repulsive force, the magnetic field direction (MD) can be formed in the same direction as the discharge direction of the negative electrode slurry. Therefore, before the negative electrode slurry is discharged onto the negative electrode collector, the carbon-based negative electrode active material (CM, in other words, graphite) contained in the negative electrode slurry can be oriented so that the [0,0,2] crystal plane is approximately horizontal relative to the negative electrode collector. Since the graphite thus oriented is coated on the negative electrode collector while maintaining an oriented state (in other words, corresponding to III: coating region), it can have a high degree of orientation without applying a separate magnetic field after coating the negative electrode slurry.
[0069] In this case, the upper lip 111 and the lower lip 121 may include an electromagnet and / or a permanent magnet to indicate magnetism. The electromagnet may include both a DC electromagnet and an AC electromagnet. In addition, the permanent magnet may include a magnet having ferromagnetic properties and a magnet having soft magnetic properties, including NdFeB-based magnets, SmCo-based magnets, ferrite magnets, Alnico magnets, FeCrCo-based magnets, Bond magnets (Nd-Fe-B, Sm-Fe-N, Sm-Co, ferrite), etc.
[0070] In addition, since the negative electrode manufacturing device applies a magnetic field before discharging the negative electrode slurry onto the electrode sheet, a weaker magnetic field can be applied compared to the case where the magnetic field is applied after the negative electrode slurry is coated on the electrode sheet. In this case, the magnetic field strength can meet a predetermined range. In other words, the upper lip 111 and the lower lip 121 can apply a magnetic field that meets a predetermined strength range when discharging the negative electrode slurry. Specifically, the upper lip 111 and the lower lip 121 can be subjected to a magnetic field having the same polarity. In this case, the applied magnetic field can have the following strength: 500G to 3,000G (Gauss), or more specifically, 500G to 2,500G; 500G to 2,000G; 500G to 1,500G; 1,000G to 2,000G; 2,000G to 2,500G; 2,000G to 3,000G; 500G to 1,500G; or 500G to 900G.
[0071] The present invention can achieve uniform crystal orientation of the carbon-based negative electrode active material before the negative electrode slurry is discharged through the groove 140 by adjusting the magnetic field strength applied to the upper lip 111 and the lower lip 121 to the above range. In addition, the present invention can maintain the degree of orientation so that the carbon-based negative electrode active material with a crystal orientation is coated on the negative electrode current collector without any change in the degree of orientation after being discharged. In addition, the present invention can prevent the magnetic field strength applied to the upper lip 111 and the lower lip 121 from exceeding the above range, so that the separation distance between the upper lip 111 and the lower lip 121 becomes smaller, thereby making it difficult to discharge the negative electrode slurry.
[0072] In addition, the slot mold 100 is crystal-oriented so that the carbon-based negative electrode active material contained in the negative electrode slurry is perpendicular to the surface of the electrode sheet 300 or the negative electrode current collector and remains oriented thereafter, or the negative electrode current collector is applied to the electrode sheet 300, and the magnetic field strength G applied to the upper lip 111 and the lower lip 121 and the width of the slot 140, in other words, the ratio of the separation distance D of the upper block 110 and the lower block 120, to meet the predetermined range. Specifically, the slot mold 100 can satisfy the following formula 1:
[0073] [Formula 1]
[0074] 0.3≤G / D≤5
[0075] In formula 1,
[0076] G represents the strength of the magnetic field applied to the upper lip and the lower lip (unit: G),
[0077] D represents the separation distance between the upper block and the lower block (unit: μm).
[0078] The orientation of the carbon-based negative active material contained in the negative electrode slurry may be affected by the applied magnetic field strength, the spacing distance of the magnets applying the magnetic field, etc. Therefore, the present invention can satisfy Formula 1 by setting the ratio (G / D) between the magnetic field strength (G) applied to the upper lip 111 and the lower lip 121 and the separation distance (D) of the upper block 110 and the lower block 120 to 0.3 to 5, so that the carbon-based negative active material contained in the negative electrode slurry can be coated and the crystal plane is oriented relative to the surface of the electrode sheet 300. More specifically, the slot die 100 may satisfy Formula 1 as follows: 0.3 to 3.0 (i.e., 0.3 ≤ G / D ≤ 3.0); 0.4 to 2.6 (i.e., 0.4 ≤ G / D ≤ 2.6); 0.5 to 1.5 (i.e., 0.5 ≤ G / D ≤ 1.5); 1.0 to 3.0 (i.e., 1.0 ≤ G / D ≤ 3.0); 1.1 to 1.9 (i.e., 1.1 ≤ G / D ≤ 1.9); 1.5 to 3.0 (i.e., 1.5≤G / D≤3.0); 2.0 to 4.0 (i.e., 2.0≤G / D≤4.0); 0.8 to 1.2 (i.e., 0.8≤G / D≤1.2); 1.2 to 1.6 (i.e., 1.2≤G / D≤1.6); 0.4 to 0.9 (i.e., 0.4≤G / D≤0.9); or 1.1 to 1.5 (i.e., 1.1≤G / D≤1.5).
[0079] In addition, the groove 140 formed by the upper lip 111 and the lower lip 121 can be positioned so that the negative electrode slurry is discharged perpendicularly to the surface of the negative electrode collector. To this end, the groove mold 100 can be positioned perpendicular to the surface of the electrode sheet 300. Preferably, as Figure 1 As shown, the groove mold 100 may include a groove 140 facing the groove mold 100, and a coating roller 200 rotatably arranged so that the electrode sheet 300 or the negative electrode collector can move with the rotation of the coating roller 200 to apply the negative electrode slurry to the surface.
[0080] The surface of the coating roller 200 may exhibit magnetism on its surface so that the carbon-based negative electrode active material of the negative electrode slurry applied to the electrode sheet 300 remains oriented in the slot mold 100. In this case, the magnetism may have a polarity different from that of the lip portions 111 and 121 of the slot mold 100. The present invention can prevent the crystal orientation of the carbon-based negative electrode active material applied to the surface of the electrode sheet 300 from being reduced by applying magnetism having a different polarity from that of the lip portions 111 and 121 of the slot mold 100 to the surface of the coating roller 200. Such magnetism can be achieved by introducing one or more of a permanent magnet and an electromagnet to the surface of the coating roller 200.
[0081] In addition, the negative electrode manufacturing device 10 according to the present invention may further include a drying section (not shown) for drying the negative electrode slurry coated on the electrode sheet 300, wherein the drying section may be arranged at a position so that the negative electrode slurry discharged from the slot mold 100 reaches the electrode sheet within 20 seconds from the time of coating on the electrode sheet, specifically 0.01 second to 20 seconds; 0.01 second to 15 seconds; 0.01 second to 10 seconds; or 0.01 second to 5 seconds.
[0082] The drying unit performs the function of removing the solvent contained in the negative electrode slurry to form the negative electrode active layer, and also performs the function of fixing the oriented carbon-based negative electrode active material inside the negative electrode slurry. To this end, the drying unit can be arranged at an appropriate position so as to dry the negative electrode slurry before the crystal orientation of the carbon-based negative electrode active material applied to the surface of the electrode sheet 300 is reduced.
[0083] In addition, the drying part is formed by including a wall (not shown) blocking the periphery except for an inlet and an outlet for introducing and leading out the electrode sheet 300 to which the negative electrode slurry is applied, and a dryer (not shown) on the wall on the side where the electrode sheet 300 coated with the negative electrode slurry is led out for drying the electrode sheet.
[0084] When the electrode sheet 300 coated with the negative electrode slurry enters through the entrance of the drying part, it receives energy provided from the opposite wall, such as light, wavelength, heat, etc. Therefore, the wall is preferably made of an insulating material so that the energy inside can be transferred to the outside and heat loss is prevented from occurring.
[0085] In addition, as long as the dryer can apply energy such as light, wavelength, heat, etc., and is conventionally used in the art, the dryer can be used without particular limitation. For example, the dryer can be used alone or in combination as an ultraviolet dryer, a near infrared dryer, a far infrared dryer, a hot air dryer, a vacuum oven, etc.
[0086] The negative electrode manufacturing device according to the present invention has the above configuration to induce the crystal orientation of the carbon-based negative electrode active material before the negative electrode slurry is discharged onto the negative electrode sheet, so that the carbon-based negative electrode active material can be coated in a state where the carbon-based negative electrode active material is oriented close to perpendicular to the surface of the negative electrode current collector. Therefore, the carbon-based negative electrode active material of the manufactured negative electrode has an excellent degree of orientation. In addition, since the above negative electrode manufacturing device does not require a separate orientation process to orient the carbon-based negative electrode active material after coating the negative electrode slurry, it has the following advantages: no additional facilities are required to manufacture the negative electrode, and it is easy to apply to large-scale production processes.
[0087] Method for manufacturing negative electrode for secondary battery
[0088] In one embodiment, the present invention also provides,
[0089] A method for manufacturing a negative electrode for a secondary battery, comprising applying a negative electrode slurry to which a magnetic field is applied to an electrode sheet using a negative electrode manufacturing apparatus according to the present invention,
[0090] Wherein, the negative electrode slurry includes a carbon-based negative electrode active material.
[0091] The method for manufacturing a negative electrode for a secondary battery according to the present invention is a method for manufacturing a negative electrode using the negative electrode manufacturing device of the present invention described above. The method for manufacturing a negative electrode includes applying a negative electrode slurry to which a magnetic field is applied to an electrode sheet. In other words, the manufacturing method is characterized in that: applying a magnetic field to a negative electrode slurry containing a carbon-based negative electrode active material and applying the negative electrode slurry to an electrode sheet (i.e., a current collector) are performed simultaneously. Therefore, the above-mentioned manufacturing method has the following advantages: after applying the negative electrode slurry, there is no need to separately perform crystal orientation of the carbon-based negative electrode active material, so the process is simple and economical, and it is easy to apply to large-scale production due to its excellent processability.
[0092] Here, the negative electrode slurry may include a carbon-based negative electrode active material magnetically oriented by the negative electrode manufacturing apparatus according to the present invention as described above, wherein the magnetic orientation may be performed by forming a magnetic field nearly perpendicular to the surface of the electrode sheet.
[0093] In addition, the manufacturing method can control the separation distance between the groove of the groove mold set in the negative electrode manufacturing device (in other words, the lip portion including the upper lip and the lower lip) and the coating roller according to the average thickness of the negative electrode slurry to be coated on the electrode sheet, so as to maintain the crystal orientation of the carbon-based negative electrode active material.
[0094] Even if the carbon-based negative electrode active material is oriented before discharge so that a specific crystal plane has a predetermined angle relative to the surface of the electrode sheet, the degree of orientation or the angle may vary depending on the fluid movement according to the angle at which the negative electrode slurry is applied to the surface of the electrode sheet during discharge. Therefore, according to the present invention, the average thickness of the negative electrode slurry applied to the electrode sheet can be adjusted to be greater than the separation distance between the groove of the groove mold provided in the negative electrode manufacturing device and the coating roller to minimize the fluid movement according to the coating angle of the negative electrode slurry during discharge. For example, the average thickness of the negative electrode slurry applied to the electrode sheet can be adjusted to 1.01 to 2.00 times; 1.01 to 1.80 times; 1.01 to 1.50 times; 1.1 to 1.5 times; or 1.2 to 1.9 times the spacing distance between the lip portion of the groove mold provided in the negative electrode manufacturing device and the coating roller. In addition, the average thickness of the negative electrode slurry applied to the electrode sheet can be 100 μm or more, more specifically, 100 μm or more but 300 μm or less; 110 μm or more but 190 μm or less; 200 μm or more but 300 μm or less; 150 μm or more but 230 μm or less; 100 μm or more but 250 μm or less; or 100 μm or more but 200 μm or less.
[0095] In addition, the negative electrode slurry applied to the electrode sheet with the magnetic field applied may be performed on the electrode sheet conveyed at a predetermined speed. The conveying speed may be the same as the speed of applying the negative electrode slurry to the electrode sheet. For example, the speed of applying the negative electrode slurry to the electrode sheet may be performed at a speed of 5 m / min to 100 m / min, more specifically, at the following speeds: 5 m / min to 35 m / min; 10 m / min to 35 m / min; 20 m / min to 35 m / min; 10 m / min to 30 m / min; 5 m / min to 20 m / min; 5 m / min to 25 m / min; or 15 m / min to 25 m / min.
[0096] The present invention can prevent the negative electrode slurry from being unevenly coated on the surface of the electrode sheet due to a significantly slower coating speed by coating the negative electrode slurry within the above speed range. At the same time, it can prevent the processing efficiency and productivity from being reduced; and it can prevent the crystal alignment state of the carbon-based negative electrode active material present in the negative electrode slurry from being destroyed due to an excessively high speed, resulting in a reduced degree of orientation.
[0097] In addition, the method of manufacturing a negative electrode for a secondary battery according to the present invention may further include applying the negative electrode slurry to which the magnetic field is applied to the electrode sheet, and then drying the applied negative electrode slurry to form a negative electrode active layer.
[0098] Forming the negative electrode active layer refers to the process of fixing the carbon-based negative electrode active material contained in the negative electrode slurry on the electrode sheet by drying the negative electrode slurry. This step is not limited to any application as long as the carbon-based negative electrode active material in the negative electrode slurry applied to the electrode sheet can be fixed and the degree of orientation relative to the surface of the electrode sheet is minimized.
[0099] Specifically, drying may be applied by applying energy such as light, wavelength, heat, etc., and drying may be performed by using an ultraviolet dryer, a near infrared dryer, a far infrared dryer, a hot air dryer, a vacuum oven, etc. alone or in combination.
[0100] Meanwhile, the carbon-based negative electrode active material contained in the negative electrode slurry may include a material conventionally coated as a carbon-based negative electrode active material in a lithium secondary battery. Specifically, a carbon-based negative electrode active material refers to a material having carbon atoms as a main component. Such a carbon-based negative electrode active material may include graphite. Graphite may include one or more of natural graphite and artificial graphite, but is preferably natural graphite, or a mixture of natural graphite and artificial graphite.
[0101] Preferably, the carbon-based negative electrode active material is a spherical graphite assembly formed by a plurality of flake graphites. Flake graphite may include natural graphite, artificial graphite, calcined carbon (blocky mesophase) based on tar and pitch, graphitized coke (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc., and preferably a plurality of highly crystalline natural graphites are gathered together. In addition, a graphite assembly may be formed by assembling 2 to 100, preferably 3 to 20 flake graphites.
[0102] This carbon-based negative electrode active material (specifically graphite) can have a spherical particle shape, wherein the sphericity of the graphite particles can be greater than or equal to 0.75 (such as 0.75 to 1.0; 0.75 to 0.95; 0.8 to 0.95; or 0.90 to 0.99). Here, "sphericity" can refer to the ratio of the shortest diameter (short diameter) to the longest diameter (long diameter) among any diameters passing through the center of the particle, where a sphericity of 1 indicates that the particle has a spherical shape. Sphericity can be measured by a particle shape analyzer. The present invention can realize a highly conductive negative electrode active layer by realizing the shape of the carbon-based negative electrode active material to be close to a spherical shape, thereby increasing the capacity of the battery. The present invention also has the following advantages: it can increase the specific surface area of the negative electrode active material, thereby increasing the adhesion between the negative electrode active layer and the current collector.
[0103] In addition, the carbon-based negative electrode active material may exhibit an average particle size (D 50 ), and more specifically, can show the following average particle size (D 50): 2μm to 7μm; 0.5μm to 5μm; or 1μm to 3μm.
[0104] The average particle size of spherical natural graphite may advantageously have a smaller particle size so that the disorder of each particle in the expansion direction is maximized to prevent the particles from expanding during lithium ion charging. However, when the particle size of natural graphite is less than 0.5 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity transmission number may be low. On the other hand, when the maximum particle size exceeds 10 μm, the expansion becomes serious, and with repeated charge and discharge, the bonding properties between particles and the bonding properties of particles to the current collector are reduced, which can significantly reduce the cycle characteristics.
[0105] In addition, the negative electrode slurry may further include a conductive material, a binder, a thickener, etc. in addition to the carbon-based negative electrode active material, and these may be applied according to those conventionally used in the art.
[0106] The conductive material may include one or more of carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, etc., but is not limited thereto.
[0107] As another example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc. as the conductive material alone or in combination.
[0108] In this case, the content of the conductive material can be 0.1 to 10 parts by weight, more specifically, 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight, relative to the total weight of the negative electrode active layer of 100 parts by weight. The present invention can control the content of the conductive material within the above range, thereby preventing the increase in the negative electrode resistance due to the low content of the conductive material, thereby reducing the charging capacity. In addition, it is also possible to prevent the problem of reduced charging capacity due to reduced content of negative electrode active materials caused by excessive conductive materials, or reduced fast charging characteristics due to increased loading of the negative electrode active layer.
[0109] In addition, a binder can be appropriately applied as a component that helps to bond the negative electrode active material to the conductive material and the negative electrode current collector without reducing the electrical properties of the electrode, but more specifically, the binder can be applied to vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber and fluorinated rubber, including any one or more thereof.
[0110] Based on 100 parts by weight of the negative electrode slurry in total, the content of the binder may be from 0.1 to 10 parts by weight, more specifically, from 0.1 to 8 parts by weight, from 0.1 to 5 parts by weight, from 0.1 to 3 parts by weight, or from 2 to 6 parts by weight. The present invention can control the content of the binder contained in the negative electrode slurry to the above range, thereby preventing the adhesion of the negative electrode active layer from being deteriorated due to low binder content, or the electrical properties of the electrode from being deteriorated due to excessive binder.
[0111] The method of manufacturing a negative electrode sheet for a secondary battery according to the present invention has the following advantages: having the above-mentioned composition, it enables the carbon-based negative electrode active material of the negative electrode slurry coated on the current collector to be uniformly aligned with a high degree of orientation.
[0112] Secondary battery negative electrode
[0113] In addition, in one embodiment, the present invention provides,
[0114] A secondary battery negative electrode prepared by the above method.
[0115] The lithium negative electrode for a secondary battery according to the present invention includes a negative electrode active layer containing a carbon-based negative electrode active material as a main component on at least one side of a current collector. The negative electrode active layer refers to a layer that embodies the electroactivity of the negative electrode. The negative electrode active layer is prepared by applying an electrode slurry including a carbon-based negative electrode active material that electrochemically embodies an oxidation-reduction reaction during battery charging and discharging to both sides of the current collector, followed by drying and rolling. Here, the negative electrode active layer is formed by applying the negative electrode slurry to which a magnetic field is applied to an electrode sheet using the above-mentioned negative electrode manufacturing device and drying, wherein the main component (carbon-based negative electrode active material) is characterized by having a high crystal orientation relative to the surface of the electrode sheet, so that the negative electrode having the negative electrode active layer has high energy density and charge and discharge performance.
[0116] Specifically, the negative electrode according to the present invention can be aligned so that the carbon-based negative electrode active material contained in the negative electrode active layer has a predetermined angle relative to the electrode sheet (or negative electrode current collector). This alignment of the carbon-based negative electrode active material can be used to reduce the degree of disorder in the negative electrode active layer, thereby reducing the electrode resistance and providing a movement path for lithium ions. At this time, the crystal orientation of the carbon-based negative electrode active material (e.g., graphite) can be determined by crystallographic analysis of the carbon-based negative electrode active material contained in the negative electrode active layer.
[0117] In one example, the negative electrode active layer may align the carbon-based negative electrode active material relative to the current collector in a certain direction so that the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer satisfies the average alignment degree of the carbon-based negative electrode active material of 0.9 or less as expressed in Formula 2 below:
[0118] [Formula 2]
[0119] OI=I 004 / I 110
[0120] In formula 2,
[0121] I 004 It represents the area of the peak representing the [0,0,4] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer,
[0122] I 110 It represents the area of the peak representing the [1,1,0] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer.
[0123] Formula 2 above can be an indicator of the degree of alignment of the crystal structure of the spherical carbon-based negative electrode active material in a certain direction (specifically, relative to the surface of the negative electrode current collector) during X-ray diffraction measurement. More specifically, the negative electrode active layer can be aligned with the peak of the carbon-based negative electrode active material (graphite) at 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2° and 77.5±0.2° representing the [0,0,2] plane, [1,0,0] plane, [1,0,1]R plane, [1,0,1]H plane, [0,0,4] plane and [1,1,0] plane, respectively. In addition, the peak appearing at 2θ=43.4±0.2° may be regarded as an overlap of peaks corresponding to the [1,0,1]R plane of the carbon-based negative active material and the [1,1,1] plane of the current collector such as copper (Cu).
[0124] Among them, the alignment degree (OI) of the carbon-based negative active material can be measured by the ratio of the peak area at 2θ = 77.5 ± 0.2° representing the [1, 1, 0] plane to the peak area at 2θ = 54.7 ± 0.2° representing the [0, 0, 4] plane, specifically, by the ratio of the areas obtained by integrating the peak intensities. Here, since the peak at 2θ = 54.7 ± 0.2° is a peak representing the [0, 0, 4] plane tilted with the negative current collector among the graphite crystal planes, the alignment degree (OI) may mean that when the value is close to 0, the inclination relative to the surface of the negative current collector is close to 90°, and when the value is larger, the inclination relative to the surface of the negative current collector is close to 0° or 180°. In this regard, the negative electrode active layer according to the present invention can have a carbon-based negative electrode active material with a low degree of alignment (OI) compared to the case where the carbon-based negative electrode active material is not self-aligned, because the carbon-based negative electrode active material is aligned so that the carbon-based negative electrode active material has an angle close to perpendicular to the negative electrode current collector, such as an angle of more than 60°, more than 70°, 70-90°, 80-90°, 65-85° or 70-85° relative to the negative electrode current collector.
[0125] When the surface of the negative electrode active layer is measured by X-ray diffraction, the negative electrode according to the present invention can have an alignment index (OI) according to Formula 2 of 0.9 or less, more specifically, it can be 0.8 or less; 0.7 or less; 0.6 or less; 0.1 to 0.9; 0.2 to 0.8; 0.3 to 0.7; 0.2 to 0.6; or 0.4 to 0.6.
[0126] In addition, the average thickness of the negative electrode active layer can be from 50 μm to 300 μm, more specifically, from 50 μm to 250 μm; from 100 μm to 250 μm; or from 100 μm to 200 μm. The present invention can not only improve the energy density of the electrode by adjusting the average thickness of the negative electrode active layer to the above range, but also uniformly control the disorder of the carbon-based negative electrode active material contained in the negative electrode active layer.
[0127] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used as the negative electrode current collector, and in the case of copper or stainless steel, carbon, nickel, titanium, silver, etc. can also be used for surface treatment. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately adopted from 1 μm to 500 μm.
[0128] Hereinafter, the present invention will be described in more detail through examples and experimental examples.
[0129] However, the following examples and experimental examples are merely illustrative of the present invention, and the present invention is not limited to the following examples and experimental examples.
[0130] Examples 1 to 5 and Comparative Examples 1 to 2. Preparation of Sheet for Secondary Battery Negative Electrode
[0131] The negative electrode active material was prepared by mixing natural graphite and artificial graphite in a weight ratio of 2:8, using carbon black as a conductive material and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as binders. The negative electrode slurry was prepared by mixing 95wt.% of mixed graphite, 1wt.% of carbon black, 1.5wt.% of carboxymethyl cellulose (CMC) and 2.5wt.% of styrene butadiene rubber (SBR) with water to make the solid content 50%.
[0132] In addition, a negative electrode manufacturing device was prepared, which includes: a slot mold in which an upper block, a spacer, and a lower block are sequentially stacked to provide a slot at the front end through which the negative electrode slurry can be discharged; and a coating roller, which is arranged to face the slot in the slot mold. At this time, the above negative electrode manufacturing device is adjusted so that i) the polarity type of the magnetism applied to the upper lip of the upper block and the lower lip of the lower block; ii) the polarity type of the magnetism applied to the coating roller; and iii) the ratio (G / D) between the magnetic field strength (G) applied to the upper lip and the lower lip and the separation distance (D) of the upper block and the lower block is as shown in Table 1 below.
[0133] The negative electrode slurry prepared in advance was injected into the prepared negative electrode manufacturing device, and the negative electrode slurry was applied to the surface of a copper thin plate (thickness: 8 μm) conveyed at a speed (M) of 10 m / min. Then, hot air was continuously applied to the applied negative electrode slurry to dry it to form a negative electrode active layer.
[0134] [Table 1]
[0135] Upper lip Lower lip Coating roller G / D Example 1 N pole N pole - 800G / 1,000μm Example 2 N pole N pole - 1,500G / 1,000μm Example 3 N pole N pole - 2,200G / 1,000μm Example 4 N pole N pole - 1,500G / 2,500μm Example 5 N pole N pole S pole 1,500G / 1,000μm Comparative Example 1 - - - - / 1,000μm Comparative Example 2 - - S pole - / 1,000μm
[0136] Experimental example
[0137] The orientation exhibited by the carbon-based negative electrode active material for a negative electrode of a secondary battery manufactured using the negative electrode manufacturing apparatus according to the present invention was evaluated.
[0138] Specifically, for each negative electrode prepared in Examples 1 to 5 and Comparative Examples 1 to 2, X-ray diffraction spectra (XRD) of any three points of the negative electrode active layer were performed, and the spectra were measured. The measurement conditions of the X-ray diffraction spectra (XRD) were as follows:
[0139] -Target: Cu (Kα-ray) graphite monochromator
[0140] - Slits: Transmitting slit = 1 degree, Receiving slit = 0.1 mm, Scattering slit = 1 degree
[0141] -Measurement section: [1,1,0] plane: 76.5°<2θ<78.5° / [0,0,4] plane: 53.5°<2θ<56.0°.
[0142] According to the spectrum measured under the above conditions, the alignment degree (OI) of each carbon-based negative electrode active material according to Formula 2 was calculated, and the average alignment degree was obtained from the calculated alignment degree (OI) of the carbon-based negative electrode active material at three points. The results are shown in Table 2.
[0143] [Formula 2]
[0144] OI=I 004 / I 110
[0145] In formula 2,
[0146] I 004 It represents the area of the peak representing the [0,0,4] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer,
[0147] I 110 It represents the area of the peak representing the [1,1,0] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer.
[0148] [Table 2]
[0149] Average alignment Example 1 0.78 Example 2 0.51 Example 3 0.54 Example 4 0.65 Example 5 0.43 Comparative Example 1 5.24 Comparative Example 2 1.97
[0150] As shown in Table 2 above, it can be seen that the negative electrode manufactured using the negative electrode manufacturing apparatus according to the present invention has a carbon-based negative electrode active material with a high degree of orientation contained in the negative electrode active layer.
[0151] This means that if the front ends of the upper and lower blocks constituting the slot mold (in other words, the lip portions) are magnetized with the same polarity when the negative electrode slurry is discharged, the crystal planes of the carbon-based negative electrode active material are oriented nearly vertically before the negative electrode slurry is applied to the electrode sheet (or negative electrode current collector), and the carbon-based negative electrode active material is coated and maintained on the electrode sheet in this oriented induced state to form a negative electrode active layer.
[0152] Judging from these results, the negative electrode manufacturing device according to the present invention has the following advantages: the carbon-based negative electrode active material in the discharged negative electrode slurry can be coated in a state where the carbon-based negative electrode active material is oriented at a predetermined angle relative to the surface of the current collector, so that the carbon-based negative electrode active material of the manufactured negative electrode not only has an excellent degree of orientation, but also has the advantage of being easy to apply to large-scale production processes.
[0153] As above, the present invention has been described in more detail through the drawings and embodiments. However, since the configuration described in the drawings or embodiments is only one embodiment of the present invention and does not represent the entire technical spirit of the present invention, it should be understood that the present invention covers various equivalents, modifications and substitutions at the time of filing this application.
[0154] Therefore, the technical scope of the present invention is not limited to the contents described in the detailed description of the specification, but should be determined by the claims of the patent.
[0155] [Description of Reference Signs]
[0156] 10: Negative electrode manufacturing device for secondary battery according to the present invention
[0157] 100: Single-die coating machine 110: Upper die
[0158] 111: Upper lip 112: Upper body
[0159] 120: Lower mold 121: Lower lip
[0160] 122: Lower body 130: Spacer
[0161] 130a: opening 140: slot
[0162] 200: coating roller 300: electrode sheet
[0163] A: Unoriented segment B: Oriented segment
[0164] I: Main body II: Lip part
[0165] III: Coating area
[0166] MD: Magnetic field direction CM: Carbon-based negative electrode active material
Claims
1. A device for manufacturing an electrode sheet, on which a negative electrode slurry containing a carbon-based negative electrode active material is coated, The negative electrode manufacturing device for a secondary battery comprises: A slot mold, the slot mold comprising an upper block, a lower block and a slot for discharging negative electrode slurry through a gap between the upper block and the lower block; as well as a coating roller, the coating roller being used to convey the electrode sheet coated with the negative electrode slurry discharged from the tank mold; The upper block and the lower block include an upper lip and a lower lip forming an outlet at their respective front ends, and the upper lip and the lower lip exhibit magnetism of the same polarity.
2. The negative electrode manufacturing device for a secondary battery according to claim 1, wherein: When the negative electrode slurry is discharged, the upper lip and the lower lip are applied with a magnetic field having an intensity of 500 G to 3,000 G.
3. The negative electrode manufacturing device for a secondary battery according to claim 1, wherein: The slot mold satisfies the following formula 1: [Formula 1] 0.3≤G / D≤5 In formula 1, G represents the intensity of the magnetic field applied at the upper lip and the lower lip, in G. D represents the separation distance between the upper block and the lower block, and the unit is μm.
4. The negative electrode manufacturing device for a secondary battery according to claim 1, wherein: The upper lip and the lower lip have a structure including at least one of a permanent magnet and an electromagnet.
5. The negative electrode manufacturing device for a secondary battery according to claim 1, wherein: The negative electrode manufacturing device further includes a drying section for drying the negative electrode slurry applied to the electrode sheet. The drying part is provided at a position where the negative electrode slurry discharged from the tank mold can reach the electrode sheet within 20 seconds from the time when the negative electrode slurry is applied to the electrode sheet.
6. A method for manufacturing a negative electrode for a secondary battery, the method comprising the following steps: The negative electrode manufacturing apparatus according to claim 1 is used to apply the negative electrode slurry to which the magnetic field is applied to the electrode sheet, Wherein, the negative electrode slurry includes a carbon-based negative electrode active material.
7. The method for manufacturing a negative electrode for a secondary battery according to claim 6, wherein: An average thickness of the negative electrode slurry applied to the electrode sheet is greater than a separation distance between the groove of the groove mold and the coating roller provided in the negative electrode manufacturing apparatus.
8. The method for manufacturing a negative electrode for a secondary battery according to claim 6, wherein: The negative electrode slurry applied to the electrode sheet has an average thickness of 100 μm or more.
9. The method for manufacturing a negative electrode for a secondary battery according to claim 6, wherein: The coating of the negative electrode slurry onto the electrode sheet is performed at a speed of 5 m / min to 100 m / min.
10. The method for manufacturing a negative electrode for a secondary battery according to claim 6, further comprising the following steps: After the negative electrode slurry is applied to the electrode sheet, the applied negative electrode slurry is dried to form a negative electrode active layer.
11. The method for manufacturing a negative electrode for a secondary battery according to claim 10, wherein: The negative electrode active layer has an alignment degree of the carbon-based negative electrode active material with respect to the surface of the electrode sheet of 0.9 or less, represented by the following Formula 2: [Formula 2] OI=I 004 / I 110 In formula 2, I 004 represents the area of the peak representing the [0,0,4] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer, I 110 It represents the area of the peak representing the [1,1,0] crystal plane in the X-ray diffraction spectrum (XRD) measurement result of the negative electrode active layer.
